2014
DOI: 10.5194/bgd-11-2933-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C, N and P stoichiometric mismatch between resources and consumers influence the dynamics of a marine microbial food web model and its response to atmospheric N and P inputs

Abstract: <p><strong>Abstract.</strong> Results from the DUNE experiments reported in this issue have shown that nutrient input from dust deposition in large mesocosms deployed in the western Mediterranean induced a response of the microbial food web, with an increase of primary production rates (PP), bacterial respiration rates (BR), as well as autotrophic and heterotrophic biomasses. Additionally, it was found that nutrient inputs strengthened the net heterotrophy of the system, with NPP : BR ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This contribution was triggered by the strength of the stoichiometric mismatch between the resource (dissolved organic matter) and bacteria. Although the model was kept simple, it highlights how stoichiometric mismatch between producers and consumers can influence the response of a planktonic food web to nutrient addition (Pondaven et al, 2014).…”
Section: Illustration Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contribution was triggered by the strength of the stoichiometric mismatch between the resource (dissolved organic matter) and bacteria. Although the model was kept simple, it highlights how stoichiometric mismatch between producers and consumers can influence the response of a planktonic food web to nutrient addition (Pondaven et al, 2014).…”
Section: Illustration Of Resultsmentioning
confidence: 99%
“…In parallel, we used a stoichiometric microbial food web model to investigate how ecological stoichiometric mismatches within the food web -that is, resources and consumers have distinct elemental composition -result in differential consumer-driven nutrient recycling (CNR; Sterner and Elser, 2002) and how, in turn, CNR feedbacks on the magnitude of the ecosystem respond to the addition of nutrients from dust (Pondaven et al, 2014). This model was used as a theoretical tool; that is, it was not optimized to fit observations from DUNE experiments.…”
Section: Illustration Of Resultsmentioning
confidence: 99%
“…We used a stoichiometric microbial food web model to investigate how the stoichiometry of consumer driven nutrient recycling (Sterner, 1990) may influence the ecosystem response to N and P dust addition. This model considers simultaneously the differential recycling of C, N and P in a food chain which includes 7 compartments (bacteria, autotrophic pico and nanoplankton, heterotrophic flagellates, ciliates and mesozooplankton) (Pondaven et al, 2013). Growth rates of bacteria and phytoplankton were controlled by the availability of dissolved inorganic and/or organic N, P and C. The model results showed that bacteria and zooplankton had substantial effects on the supply rate and the stoichiometry of N and P in the dissolved pools, thereby exerting a control Figures on the predicted primary production.…”
Section: Special Issue Presentationmentioning
confidence: 99%